E-Business and Collaboration: A Literature Study - Wahyu Dwi Putra Wahyu (Institute of Information Technology and Social Science (IITSS), 2023)
E-business represents a business approach that leverages hardware, software, network, and human resources to conduct business interactions, transactions, and operations across organizations without time and space limitations. E-commerce is a subset of e-business that focuses on commercial transactions, while e-business encompasses broader elements such as business partnerships, customer services, and recruitment processes. The advancement of information technology provides convenience in daily business operations; however, barriers remain, including trust in digital systems, security risks, and financial constraints. This paper aims to provide foundational understanding for e-commerce entrepreneurs to develop their business through effective collaboration among companies and individuals. This study also emphasizes the role of information systems, collaborative networks, and organizational integration in optimizing e-business efficiency within the framework of Industry 4.0.